REMEDIATION CAPACITY OF AQUATIC PLANTS FOR REDUCING ORGANIC LOAD AND NUTRIENTS IN NILE TILAPIA AQUACULTURE WASTEWATER - Devi Ulinuha; Ima Yudha Perwira (Universitas Mataram, 2026)
Nile tilapia aquaculture wastewater has the potential to pollute aquatic environments if it is discharged without prior treatment. This study aimed to evaluate the remediation capacity of selected aquatic plants in reducing organic load and nutrients in Nile tilapia aquaculture wastewater. The aquatic plants used in this study were water hyacinth (Eichhornia crassipes), yellow velvetleaf (Limnocharis flava), water spinach (Ipomoea aquatica), and water lettuce (Pistia stratiotes). The control treatment consisted of wastewater without aquatic plants. Each treatment was performed in triplicate to obtain the mean and standard deviation values. The measured water quality parameters included total organic matter (TOM), nitrate, phosphate, bacterial abundance, dissolved oxygen (DO), pH, total dissolved solids (TDS), and turbidity. Leaf chlorophyll content of the aquatic plants was also measured. The results showed that water hyacinth reduced TOM by up to 37.5 ± 1.2%. Water spinach reduced nitrate by 81.0 ± 1.6%, while phosphate decreased by 79.4 ± 5.0%. The water spinach treatment showed the highest bacterial abundance on day 14, with an increase of (35.7 ± 2.0) × 10³ CFU/mL from the initial value. This treatment also had the lowest reduction in leaf chlorophyll content, at 6.7 ± 2.9%. Water quality conditions after the remediation process met the water quality standards for aquaculture. These findings indicate that water spinach and water hyacinth were the most effective aquatic plants for reducing organic load and nutrients, particularly nitrate and phosphate. Water spinach also showed relatively high tolerance to Nile tilapia aquaculture wastewater and was able to maintain its photosynthetic pigments under wastewater stress conditions.